Bacteriological Profile of Neonatal Sepsis in a Tertiary Hospital in Bangladesh (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Objectives: To evaluate the common pathogens associated with neonatal sepsis in a tertiary care hospital in Bangladesh and their antibiotic susceptibility pattern. Materials and Method: This prospective study was done at Special Care Baby Unit (SCABU) BIRDEM Hospital from January to December 2008. Neonates whose blood culture yielded growth of bacteria were included in this study. Results: Sepsis was associated with Low Birth Weight and common organism isolated was Klebsiella and Enterobacter Ampicillin, Genatamicin and third generation cephalosporin were almost resistance to all organisms. Conclusion: Bacterial profile is not the same as western countries, Gram-negative bacteria and in particular Klebsiella and enterobacter species are the leading causes of neonatal sepsis and resistance to ampicillin, gentamicin and third generation cephalosporin   DOI: http://dx.doi.org/10.3329/jbcps.v30i2.11406   J Bangladesh Coll Phys Surg 2012; 30: 66-70